About one class of Hilbert space uncoditional bases
Let a sequence {v_k }^+∞_-∞l_2 and a real sequence {λ_k }^+∞_-∞ such that {λ_k^-1 }^+∞_-∞l_2, and an orthonormal basis {e_k }^+∞_-∞ of a Hilbert space be given. We describe a sequence M={μ_k }^+∞_-∞, MR=, such that the families f_k = _jZ v_j(λ_j-μ_k )^-1 e_k, kZ form an unconditional basis in H., number=3, journal=Methods of Functional Analysis and Topology, author=Volkova, M. G. and Tarasenko, A. A., year=2007, month=Sep., pages=296–300